Complex antigen presentation pathway for an HLA-A*0201-restricted epitope from Chikungunya 6K protein - Lorente, Elena; Barriga, Alejandro; García-Arriaza, Juan; Lemonnier, François A.; Esteban, Mariano; López, Daniel (PLOS Neglected Tropical Diseases, 2017)
Author summary The arboviral pathogen Chikungunya virus (CHIKV) is a serious threat to global health, and is considered a priority re-emerging virus. This pathogen causes acute febrile infection in patients, leading to debilitating arthralgia and arthritis. In recent years, CHIKV has spread quickly in tropical and subtropical countries, causing outbreaks of more severe forms of the disease than previously reported. The nature and function of the T cell immune response, critical for clearance of viral infections, is largely unknown during acute and chronic CHIKV disease and their association with rheumatic disorders. In this study, we identified the three first CHIKV epitopes recognized by human T cells. We studied how one of these epitopes is generated in virus-infected cells, a process that involves the sequential proteolytic activity of several proteases at distinct subcellular locations. We postulate that this process could have broad implications when applied to other viral proteins.